Making Up for Harming Others — An Experiment on Voluntary Compensation Behavior - Frauke Stehr; Peter Werner (ZBW - Leibniz Information Centre for Economics, 2021)
We study to what extent consumers forego personal gains to avoid or reduce the harm their choices impose on others. In the absence of regulation, such voluntary compensation provides a way for consumers to internalize negative externalities on their own. However, the tangibility of consumption externalities is often reduced by diffusion of both the harm created and the responsibility in creating the externality. We conduct a laboratory experiment to investigate how the presence of diffusion affects voluntary compensation. We find that subjects are generally willing to compensate at least some of the harm their consumption creates for other subjects. Diffused responsibility for the externality, however, reduces compensation levels and leads to larger overall net externalities as compared to a baseline condition without diffusion. Diffusion of the harm caused by consumption, on the other hand, does not change compensation choices and externalities. Overall, while the introduction of voluntary compensation reduces the harm created by consumption, the net externality still remains high across all treatments.
Keywords: D91; D62; H41; Q58; 330; voluntary compensation; diffused responsibility; diffused harm; socially-responsibleconsumption